BOOK REVIEW OF “THE TIME KEEPER” WRITTEN BY MICTH ALBOM - Saputra, Ginanjar (LANTERN (Journal on English Language, Culture and Literature), 2016)
“Time is money” is one of the most popular phrases in the world. Nowadays, human life depends on time as it is everything. According to history, the time creator was humans. After knowing how to count time, they became afraid about time, out of time, and they became aware about keeping time, saving time. Humans became selfish about time. Their ego made them want time to be faster or slower. They are afraid about their age, to be old, to be dead. Another wants to die, and some want it to come faster and soon. It is all because of their knowledge about time, after they know how to count it.